Electrical storm reveals worse prognosis compared to myocardial infarction complicated by ventricular tachyarrhythmias in ICD recipients - Müller, Julian; Behnes, Michael; Schupp, Tobias; Ellguth, Dominik; Taton, Gabriel; Reiser, Linda; Engelke, Niko; Borggrefe, Martin; Reichelt, Thomas; Kern-Bollow, Armin; El-Battrawy, Ibrahim; Weidner, Kathrin; et al. (Heart and vessels, 2021)
Both acute myocardial infarction complicated by ventricular tachyarrhythmias (AMI-VTA) and electrical storm (ES) represent life-threatening clinical conditions. However, a direct comparison of both sub-groups regarding prognostic endpoints has never been investigated. All consecutive implantable cardioverter-defibrillator (ICD) recipients were included retrospectively from 2002 to 2016. Patients with ES apart from AMI (ES) were compared to patients with AMI accompanied by ventricular tachyarrhythmias (AMI-VTA). The primary endpoint was all-cause mortality at 3 years, secondary endpoints were in-hospital mortality, rehospitalization rates and major adverse cardiac event (MACE) at 3 years. A total of 198 consecutive ICD recipients were included (AMI-VTA: 56%; ST-segment elevation myocardial infarction (STEMI): 22%; non-ST-segment myocardial infarction (NSTEMI) 78%; ES: 44%). ES patients were older and had higher rates of severely reduced left ventricular ejection fraction (LVEF) < 35%. ES was associated with increased all-cause mortality at 3 years (37% vs. 19%; p = 0.001; hazard ratio [HR] = 2.242; 95% CI 2.291-3.894; p = 0.004) and with increased risk of first cardiac rehospitalization (44% vs. 12%; p = 0.001; HR = 4.694; 95% CI 2.498-8.823; p = 0.001). This worse prognosis of ES compared to AMI-VTA was still evident after multivariable adjustment (long-term all-cause mortality: HR = 2.504; 95% CI 1.093-5.739; p = 0.030; first cardiac rehospitalization: HR = 2.887; 95% CI 1.240-6.720; p = 0.014). In contrast, the rates of MACE (40% vs. 32%; p = 0.326) were comparable in both groups. At long-term follow-up of 3 years, ES was associated with higher rates of all-cause mortality and rehospitalization compared to patients with AMI-VTA.
Gesehen am 04.01.2023